The King of Adobe : Reies López Tijerina, Lost Prophet of the Chicano Movement - Oropeza, Lorena, 1964- (Book collections on Project MUSE., 2019)
"The King of Adobe offers a fresh and unvarnished look at the life of Reies López Tijerina (1926-2015), one of the most controversial, criticized, and misunderstood Chicano Movement leaders of the 1960s. Directly addressing allegations of anti-Semitism, accusations of sexual abuse, as well as evidence of extreme religiosity and possible mental illness, the book captures the life a man who changed our understanding of the American West"--